Neural Networks and Artificial Intelligence 8th International Conference, ICNNAI 2014, Brest, Belarus, June 3-6, 2014. Proceedings - Golovko, Vladimir; Imada, Akira; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Neural Networks and Artificial Intelligence, ICNNAI 2014, held in Brest, Belarus, in June 2014. The 19 revised full papers presented were carefully reviewed and selected from 27 submissions. The papers are organized in topical sections on forest resource management; artificial intelligence by neural networks; optimization; classification; fuzzy approach; machine intelligence; analytical approach; mobile robot; real world application.
Forest resource management -- Artificial intelligence by neural networks -- Optimization -- Classification -- Fuzzy approach -- Machine intelligence -- Analytical approach -- Mobile robot -- Real world application.
Keywords: Computer science; Data mining; Artificial intelligence; Pattern recognition; Application software; Computer Science; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Computer Applications; Data Mining and Knowledge Discovery; Electronic books